2022
DOI: 10.1002/anie.202213646
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Defluorinative Coupling of Difluoroalkenes and Aryl Boronic Acids for Ketone Synthesis

Abstract: The transition‐metal‐catalyzed carbonylation reaction is a useful approach for ketone synthesis. However, it is often problematic to use exogenous carbonyl reagents, such as gaseous carbon monoxide. In this manuscript, we report a novel palladium‐catalyzed coupling reaction of gem‐difluoroalkenes and aryl boronic acids that yields bioactive indane‐type ketones with an all‐carbon α‐quaternary center. Characterization and stoichiometric reactions of the key intermediates RCF2PdII support a water‐induced defluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…This product is likely generated from an oxyamination‐hydrolysis pathway. Thus, ( E )‐4‐aminobut‐2‐enoates were isolated in good yields under these modified reaction conditions ( 63 – 65 , Scheme 3), which offered a new strategy to yield a range of racemic γ‐amino α, β‐unsaturated carboxylic acid esters [22] . The asymmetric version of this reaction, however, failed after extensive attempts.…”
Section: Resultsmentioning
confidence: 99%
“…This product is likely generated from an oxyamination‐hydrolysis pathway. Thus, ( E )‐4‐aminobut‐2‐enoates were isolated in good yields under these modified reaction conditions ( 63 – 65 , Scheme 3), which offered a new strategy to yield a range of racemic γ‐amino α, β‐unsaturated carboxylic acid esters [22] . The asymmetric version of this reaction, however, failed after extensive attempts.…”
Section: Resultsmentioning
confidence: 99%
“…Further screening demonstrated that employing DMF as solvent further increased the efficiency of the reaction resulting in a 78% yield of 3 a (Table 1, entries 13-21). [14] Aiming to reduce the degradation of boronic acid species, we tested the slow release of the boronic acid precursor using protected groups such as the pinacol ester, [11][12] but no reaction was observed (Table 1, entry 22). Additional assessment of the reaction conditions including the use of H 2 O as an additive, or variation of the oxidant source did not lead to improved yields (Table S2, ESI).…”
Section: Resultsmentioning
confidence: 99%
“…At this stage, a variety of bases were evaluated (Table 1, entry 9–13) revealing that carbonates – p K a around 10 [13] – were most effective with the use of a Zn‐counterion leading to the highest observed yield. Further screening demonstrated that employing DMF as solvent further increased the efficiency of the reaction resulting in a 78% yield of 3 a (Table 1, entries 13–21) [14] . Aiming to reduce the degradation of boronic acid species, we tested the slow release of the boronic acid precursor using protected groups such as the pinacol ester, [11–12] but no reaction was observed (Table 1, entry 22).…”
Section: Resultsmentioning
confidence: 99%
“…. 54 An oven-dried 100 mL round-bottom flask equipped with a stir bar was charged with 2-iodobenzaldehyde (462 mg, 2.0 mmol) and acetophenone (240 mg, 1.0 mmol) in ethanol (10 mL). To the solution was added NaOH (60 mg, 1.5 mmol) at 0 °C.…”
Section: Preparation Of (E)-3-(2-iodophenyl)-1-phenylprop-2-en-1-one ...mentioning
confidence: 99%